Analysing the inhibitors of complexity for achieving sustainability and improving sustainable performance of petroleum supply chain. (10th August 2021) - Tarei, Pradeep Kumar; Chand, Pushpendu; Gangadhari, Rajan Kumar; Kumar, Anil
Abstract: In the era of business sustainability, the modern supply chain is becoming complex due to several inhibitors such as uncertainty in the market, technological innovation, environmental protocols, cross-border trade regulations, and many stakeholders' involvement. In the existing literature, minimal discussion to study the inhibit supply chain complexity (SCC) inhibitors for achieving sustainability. Therefore, the study analyses the inhibitors to SCC and supply chain sustainability (SCS) jointly. The combined examination of the underlying relationship for improving the Petroleum Supply Chain's sustainable performance (PSC) is arguably one of the complex sectors with a significant impact on the environment and sustainability. The inhibitors to SCC and SCS are identified through extensive literature review and experts' opinions. Through a structured questionnaire, data were collected from PSC experts. An integrated approach of analytic hierarchy process (AHP) and interpretive structural modelling (ISM) is proposed to prioritize and examine the underlying relationship between inhibitors. This study explores the driving and dependence power of the inhibitors. The results indicate that most of the SCS inhibitors, such as institutional pressures (laws and regulations), strategic lack of strategic supplier alliance, market threat, act as drivers of SCC inhibitors, such as technological complexity, horizontal complexity, and complexity of customers. The study's findings would help the supply chain managers and the petroleum sector policymakers to make better decision to overcome the challenges for achieving sustainability in PSC. Highlights: Analysed the inhibitors to SCC and SCS jointly for improving performance of Petroleum Supply Chain (PSC). Proposed an integrated approach of AHP and ISM to prioritize and examine the underlying relationship between inhibitors. Explored the driving and dependence power of the inhibitors of SCC and SCS. Findings would help the managers and policymakers of the petroleum sector for achieving sustainability.